PENDISTRIBUSIAN BANTUAN PANGAN NON TUNAI (BPNT) BERDASARKAN PERATURAN PRESIDEN NOMOR 63 TAHUN 2017 TENTANG PENYALURAN BANTUAN SOSIAL SECARA NON TUNAI OLEH DINAS SOSIAL KABUPATEN SOLOK - Cetrayon Cetrayon; Eva Suryany; Skoldan Skoldan (Jurnal Public Administration, Business and Rural Develoment Planning, 2023)
The research objectives are: 1) To find out how the distribution of BPNT is based on Presidential Regulation Number 63 of 2017 concerning the Distribution of Non-Cash Social Assistance by the Social Service of Solok Regency. 2) To find out what factors influence the distribution of BPNT based on Presidential Regulation Number 63 of 2017 concerning the Distribution of Non-Cash Securu Social Assistance by the Solok Regency Social Service. This study uses a descriptive method, where the researcher tries to describe all phenomena, symptoms, events according to the research problem as it is. Based on the descriptions in the previous chapters, the authors draw the following conclusions: 1) The distribution of BPNT based on Presidential Regulation Number 63 of 2017 concerning Non-Cash Distribution of Social Assistance by the Social Service of Solo Regency consists of program preparation, coordination of implementation, implementation of beneficiary registration , submission of beneficiary data, registration and/or opening of kurtu combo beneficiary accounts, distribution/distribution of aid and utilization. 2) Factors affecting the distribution of BPNT based on Presidential Regulation Number 63 of 2017 concerning Non-Cash Distribution of Social Assistance by the Solak District Social Service, including data errors, empty balances and socialization. Based on the conclusions above, the authors provide the following suggestions: 1) The data collection should be carried out evenly and on target so that the prospective Beneficiary Families (KPM) are in accordance with the predetermined sam, 2) It is hoped that all deficiencies can be corrected and not continuous. occurs so that the goals of BPNT that have been previously set can be achieved to the maximum. 3) There should be more routine socialization activities to do.